2018
DOI: 10.2174/1874836801812010132
|View full text |Cite
|
Sign up to set email alerts
|

Ultimate Performance of External End-plate Bolted Joints Under Column Loss Scenario Accounting for the Influence of the Transverse Beam

Abstract: Background: Steel beam-to-column joints are generally designed and analysed considering the response parame-ters in their main bending plane, disregarding the influence of the connections and the related beams in the transverse direction. However, the 3D response of the joint can be influenced by the presence of the transverse beams in the case of column loss scenario. Objective: The objective of the study is to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Many Italian reaserch projects, numerical and analytical studies demonstrated the ability of steel systems to show very good structural [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Many Italian reaserch projects, numerical and analytical studies demonstrated the ability of steel systems to show very good structural [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The use of double-tee profiles for the structural members of steel moment-resisting frames (MRFs) is widespread in Europe and the USA. This large use is due to the existence of reliable formulations able to predict, in a very accurate way, the mechanical behaviour of I- or H-shape members, but also to the possibility to adopt a wide range of easy-to-construct beam-to-column connections [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Additionally, for most of the existing beam-to-column connection solutions, the flexural strength and stiffness can be accurately predicted by applying the component method [ 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Seismic behavior of structures has been a key topic in the last decades and still under investigation. The University of Naples “Federico II” carried out research devoted to the evaluation of dynamic properties and seismic response of both traditional steel structures [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ] and lightweight steel systems [ 22 , 23 , 24 , 25 , 26 ]. In this framework, an important research project funded by Lamieredil S.p.A. company, recently finished, which the main goal was the investigation of seismic behavior of lightweight steel (LWS) constructions and in particular cold-formed steel (CFS) strap-braced wall buildings.…”
Section: Introductionmentioning
confidence: 99%